Гарантування інформаційної безпеки в умовах російської агресії проти України - Тараненко, Ганна Геннадіївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Information security is one of the important components of guaranteeing national and international security. Challenges to information security in today’s world are extremely serious - from cyberattacks and cyberaggression to manipulation of the consciousness of social groups and interference in elections. Guaranteeing Ukraine’s information security and developing resilience to information threats is an important dimension of the ongoing Russian-Ukrainian war. The measures should be aimed at both external and internal audiences with appropriate information messages and appeals. The use of successful international experience and the mutually enriching exchange of ideas with international allies and partners are the key to increasing Ukraine’s resilience to information challenges under the ongoing Russian aggression.